EARLY DETECTION AND PREVENTION OF DEGENERATIVE DISEASES TO IMPROVE THE QUALITY OF LIFE OF ELDERLY IN MOJOROTO: DETEKSI DINI PENYAKIT DEGENERATIF DAN PENCEGAHANNYA GUNA MENINGKATKAN KUALITAS HIDUP LANSIA MOJOROTO - Mardiana Prasetyani Putri; Frieti Vega Nela; Anik Andayani; Nita Ermawati; Hartati Tuna; Arshy Prodyanatasari; Asih Imulda (PT. ROCE WISDOM ACEH, 2026)
The increasing elderly population in Mojoroto District, Kediri City, elevates the risk of degenerative diseases such as diabetes mellitus, gout, and hypercholesterolemia, which can significantly decrease their quality of life. This community service program aimed to empower the elderly through interactive education on early detection, free health screenings, and the introduction of Caesalpinia sappan L. (secang) herbal drinks as a preventive measure. The method involved a planning phase, interactive educational sessions, free medical tests for blood glucose, uric acid, and cholesterol, and a short-term evaluation phase. The results showed that 90% of the participants experienced an increase in post-educational knowledge scores. Health screenings covered 85% of the total elderly population in the community, successfully identifying that 30% of participants had blood parameter values above the normal threshold without prior awareness. Furthermore, 65% of the elderly showed high interest in routinely consuming secang herbal tea. This program effectively established a community-based preventive health framework, demonstrating that an integrated screening approach combined with local traditional wisdom can substantially enhance the quality of life and health independence of urban elderly groups.